2014
DOI: 10.1097/mib.0000000000000144
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the Colonic Deposition of Free Hemoglobin-α Chain

Abstract: Purpose We analyzed inflamed mucosal/submucosal layers of ulcerative colitis (UC=63) and Crohn’s colitis (CC=50) and unexpectedly we unveiled a pool of free-hemoglobin-alpha (Hb-α) chain. Patients with colitides have increased ROS, DNA-oxidation products, free-iron in mucosa, in pre-neoplastic, and in colitis-cancers and increased risks of developing colorectal-cancer (CRC). All IBD-related-CRC lesions are found in segments with colitis. Linking this information we investigated whether free-Hb-α is key transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 127 publications
0
35
0
Order By: Relevance
“…Five colon tissue protein extracts and staining of HD5 per disease by immunohistochemistry (IHC) was done as previously described. 24 Quantification of HD5 staining was analyzed manually by microscopy and automatically quantified using Nikon's Eclipse Ti microscope with built-in NEARAS [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Five colon tissue protein extracts and staining of HD5 per disease by immunohistochemistry (IHC) was done as previously described. 24 Quantification of HD5 staining was analyzed manually by microscopy and automatically quantified using Nikon's Eclipse Ti microscope with built-in NEARAS [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated that nitrergic neurons are degenerated in colitis (Onori et al, 2005; Sung et al, 2006). Recent studies from our laboratory indicate that nNOS, as well as antioxidants (NRF2 regulated-Phase II enzymes) protein expression are down-regulated in diseased colon specimens (Myers et al, 2014; Gangula et al, 2017). Furthermore, our previous studies demonstrated that polybacterial infection led to a decrease in nNOS, NRF2 and antioxidants protein expression in the colon tissues (Gangula et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although not yet described in the intestine, non-erythroid hemoglobin expression has been reported in various cell types where it exerts antimicrobial activity and plays a role in oxidative and nitrosative stresses [ 53 ]. Considering the hematologic abnormalities associated with the development of NEC [ 1 , 2 ], future investigation of hemoglobin is needed in light of a recent study that reported a toxic effect of α-hemoglobin on colonic epithelial cells [ 54 ].…”
Section: Discussionmentioning
confidence: 99%